A Study of Performance of SIDBI in the Development of MSMEs in India - Keshav Mishra; Prof. Jai Shanker Shukla (International Journal of Engineering and Management Research, 2022)
The Micro, Small, and Medium-Sized Enterprises (MSMEs) sector has a significant impact on the expansion of the Indian economy. On April 2, 1990, the Indian government formed the Small Industries Development Bank of India (SIDBI) to fulfil the financial, development, and promotion requirements of the MSMEs sector. The SIDBI acts as a nodal organisation, facilitator, and accelerator for the expansion of MSMEs. Secondary sources were used in the research. The majority of the information was taken from the SIDBI Annual Reports. According to the report, the majority of performance ratios and indicators have an upward trend and a positive growth rate, which shows how effectively SIDBI has performed. The bank will undoubtedly achieve new heights in the MSMEs sector over the ensuing years.